Swelling Kinetics and Rheological Characterization of Methyl Acrylate-Vinyl Acetate-Acrylic Acid Hydrogels - Aslam Malana, Muhammad; Firdous, Gulistan; Javed, Abeera; Iqbal Zafar, Zafar; Saleem Khan, Muhammad (Asian Journal of Chemistry, 2014)
In the present studies, swelling kinetics of crosslinked methyl acrylate-vinyl acetate-acrylic acid (MA-VA-AA) hydrogels and rheological studies of uncrosslinked MA-VA-AA hydrogels have been undertaken. The swelling response of hydrogels to pH, temperature and concentration of methyl acrylate has been investigated. It was observed that equilibrium swelling (we) increased with pH and temperature whereas, it decreased with methyl acrylate contents. The value of 0.5 < n < 1 obtained in the present studies at all the temperatures, pH and methyl acrylate concentrations indicated non-fickian mechanism of the diffusion process. In order to evaluate kinetic order of swelling, Fick's model and Schott's model were applied to the experimental data. Better value of correlation coefficient (R2 > 0.96) obtained in case of Fick’s model showed that swelling behavior of the hydrogels followed first order kinetics. The values of fluidity index (n) obtained from the flow curves at all the temperatures were less than 1.0 indicating non-newtonian behavior of all the hydrogels. The magnitude of Bingham yield stress increased with methyl acrylate concentration and decreased with temperature. Consistency coefficient (K), however, increased with methyl acrylate concentration. This could be interpreted in terms of higher degree of entanglement in the gel containing greater contents of methyl acrylate. Maximum swelling of MA-VA-AA hydrogel at pH 8 suggests that it may be used as drug delivery device for delivering drug at colonic part of intestine (pH 7-8).